Insight, Neurocognition, and Schizophrenia: Predictive Value of the Wisconsin Card Sorting Test - Stratton, John (Hindawi Publishing Corporation, 2013)
Lack of insight in schizophrenia is a key feature of the illness and is associated with both positive and negative clinical outcomes. Previous research supports that neurocognitive dysfunction is related to lack of insight, but studies have not examined how neurocognition relates to change in insight over time. Therefore, the current study sought to understand how performance on the Wisconsin Card Sorting Test (WCST) differed between participants with varying degrees of change in insight over a 6-month period. Fifty-two patients with schizophrenia or schizoaffective disorder were administered the WCST and Positive and Negative Syndrome Scale (PANSS) at baseline, and the PANSS was again administered at a 6-month follow-up assessment. Results indicated that while neurocognition was related to insight at baseline, it was not related to subsequent change in insight. The implications of findings for conceptualization and assessment of insight are discussed.